2001
DOI: 10.1039/b104522a
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic asymmetric heterogeneous aziridination of styrene using CuHY: effect of nitrene donor on enantioselectivity

Abstract: The copper-catalysed aziridination of styrene with copper-exchanged zeolite Y (CuHY) and copper() triflate (trifluoromethanesulfonate) (Cu(OTf ) 2 ) as catalysts is described in detail. Two nitrene donors, [N-( p-tolylsulfonyl)imino)]phenyliodinane (PhI᎐ ᎐ NTs) and [N-( p-nitrophenylsulfonyl)imino]phenyliodinane (PhI᎐ ᎐ NNs) are compared. Modification of the catalyst with bis(oxazolines) affords enantioselective catalysts and a range of chiral bis-(oxazolines) has been studied. The ratio of nitrene donor to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
58
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 28 publications
4
58
1
Order By: Relevance
“…Sulfur analysis of the residue after exchange shows that part of the triflate remains on the solid, probably due to substitution of only one of the triflate counter-ions of 4-Cu(OTf) 2 with the anionic centers of the solid. Several authors have described that the reaction results are strongly dependent on the reaction conditions, 4,6,12 in particular the relative amounts of styrene, nitrene precursor, Cu salt and chiral ligand. Therefore we tried to optimize the results in homogeneous phase before applying the immobilized catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Sulfur analysis of the residue after exchange shows that part of the triflate remains on the solid, probably due to substitution of only one of the triflate counter-ions of 4-Cu(OTf) 2 with the anionic centers of the solid. Several authors have described that the reaction results are strongly dependent on the reaction conditions, 4,6,12 in particular the relative amounts of styrene, nitrene precursor, Cu salt and chiral ligand. Therefore we tried to optimize the results in homogeneous phase before applying the immobilized catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…95 %, can be designed on this basis. [7] In addition, we have shown that the copper bis(oxazoline) complex, when constrained within the zeolite structure, [8] gives substantially higher enantioselection than the homogeneous catalysts. [7,9] Similar effects have been noted for other immobilized catalysts.…”
mentioning
confidence: 97%
“…[7] In addition, we have shown that the copper bis(oxazoline) complex, when constrained within the zeolite structure, [8] gives substantially higher enantioselection than the homogeneous catalysts. [7,9] Similar effects have been noted for other immobilized catalysts.[10] We have now found that bis(oxazoline)-modified CuH zeolite Y catalysts are extremely effective catalysts for asymmetric carbonyl-and imino-ene reactions and, furthermore, these catalysts can be readily recovered and reused without loss of catalyst performance.The reaction of ethyl glyoxylate with a range of alkenes has been investigated using the immobilized copper-zeolite Y (Cu-HY) bis(oxazoline) catalyst and the results are shown in Table 1. In the absence of the bis(oxazoline), negligible reaction was observed.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In general, this "heterogenisation" has taken place using differential catalyst solubility approaches, [24][25] as well as through the use of non-covalent, [26][27] or covalent, [27][28][29][30][31][32][33] interactions between the molecular catalyst and the surface of the solid material either following modification of the surface of the solid or the catalytic material or both.…”
Section: Introductionmentioning
confidence: 99%